REDUCTION OF ACTIVE POWER LOSS BY PIONEERING POLL ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2017)
This paper projects Pioneering Poll (PP) algorithm, which inspired by poll around the world is used to solve optimal reactive power problem. In Pioneering Poll (PP) algorithm population is general people and each person may be a candidate or a voter. Definite number of people will form dissimilar groups to set up political parties in the solution space. Advertising movement is the fundamental of this Pioneering Poll (PP) algorithm and it contains three core phases: sanguine campaign, disparate campaign and union campaign. During sanguine campaign, the nominee proclaims themselves through accentuate their positive descriptions and potentials. In the disparate campaign, candidates challenge with each other to raise their status and malign their contender. In extraordinary cases, the candidates that have equivalent information can united together in order to increase the possibility of success of the joint party. Campaign positively grounds the people to congregate to a state of solution space that is the comprehensive optimum. All these determinations lead up to poll day (end condition). On poll day, the candidate who is acquiring maximum votes is proclaimed as the conqueror and it matches to the supreme solution that is found for the reactive power problem. The proposed Pioneering Poll (PP) algorithm has been tested in standard IEEE 118 & practical 191 bus test systems and simulation results show clearly about the enhanced performance of the proposed Pioneering Poll (PP) algorithm in reducing the real power loss with voltage profiles are within the limits.